Formulasi dan Evaluasi Sediaan Sabun Padat Antiseptik Ekstrak Etanol Daun Kunyit - Suprianto; Sumardi; Debi Meilani; Sri Rahayu (Jurnal Indah Sains dan Klinis, 2022)
The plant of findings turmeric (Curcuma longa) are often used as a traditional medicinal. The part of the turmeric plant that is often used is the rhizome. In addition to turmeric rhizome, turmeric leaves are also used as a flavoring dish. Among the benefits of turmeric leaves is as an antimicrobial. Soap is a surfactant used for washing and cleaning. Antiseptics are inhibitors for the growth and development of microorganisms that live on the surface of the body. The study was to determine which ethanol extract of turmeric leaves could be formulated into antiseptic solid soap preparations. This study used an experimental method, turmeric leaves were extracted with 70% ethanol. The formula made are 2.5%, 5%, 7.5%. The quality of the soap preparation was carried out by organoleptic tests, acidity, high foam and irritation. The results test showed that the solid soap did not have the aroma of turmeric leaves, the pH of the soap was 9.9-10.5; foam height with a concentration of 7.5% which is 7.3 cm; and solid soap preparations ethanol extract of turmeric leaves did not cause irritation. The extract of turmeric leaves can be formulated into solid soap preparations. It is recommended to add perfume to the formulation of solid soap preparations of turmeric leaf extract as an antiseptic.